Study on the Influence of SiO2 on Silicone Rubber Material Used in Cable Accessories. Issue 1 (1st December 2022) - Zhao, Xuefeng; Han, Jiarui; Pu, Lu; Duan, Wei; Ju, Zeli; Sun, Haofei; Gao, Jian
Abstract: Silicone rubber is an insulating material widely used in DC cable accessories. Its interface is a weak area of insulation. Hydrated silica (SiO2 ·H2 O) is a reinforcing agent commonly used in SR, and its main component is SiO2 . Based on the theory of nano-composite dielectric, four kinds of composite silicone rubber samples with different filler contents were prepared by taking silica as the filler and liquid silicone rubber as the matrix. The properties of composite samples were tested. It is found that nano-modification can optimize the surface morphology distribution characteristics of silicone rubber, reduce the roughness, improve the tensile strength, and deepen the trap energy distribution of silicone rubber. The results of the research provide help for the design of DC cable accessories.